Pengaruh Kepemimpinan Transformasional Dan Kepemimpinan Transaksional Terhadap Organizational Citizenship Behavior - Meilaty Finthariasari; Karyono; Santi Anisa Putri (CV. Ulil Albab Corp, 2022)
This study aims to analyze transformational leadership and transactional leadership on organizational citizenship behavior either partially or simultaneously. The study was conducted on employees of Central Bengkulu General Hospital with a total sample of 105 employees. In this study the authors used quantitative methods and data collection techniques by means of observation, interviews and questionnaires.Based on the results of research using the SPSS version 22 program. It can be concluded that Transformational Leadership (X1) and Transactional Leadership (X2) have a positive effect on Organizational Citizenship Behavior (Y). The results of multiple linear regression analysis obtained the following equation: Y = 2.823 + 0.378 (X1) + 0.811 (X2) and the coefficient of determination of R2 = 0.565 or 56.5%. Based on the results of the hypothesis test, namely the t test (partial) and the F test (simultaneous), the significance value of Transformational Leadership and Transactional Leadership is = 0.000. It means that the Fsig value < 0.05, then together these variables have a positive and significant effect on Organizational Citizenship Behavior.